(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2025)
This article analyzes the process of Uzbekistan’s accession to the World Trade Organization (WTO) and its impact on the country’s economy. Uzbekistan’s accession to the WTO creates opportunities for integration into the global economy, entering the international trade environment, and enhancing competitiveness. However, this process also has both positive and negative aspects, which are examined as risks and opportunities. The article analyzes the risks, strategies, and necessary political, economic, and institutional measures for the successful implementation of Uzbekistan’s accession to the WTO.